Growth of carbon nanowalls at atmospheric pressure for one-step gas sensor fabrication - Zhu Yanwu; Ruoff Rodney; Chen Xinqi; Yu Kehan; Bo Zheng; Lu Ganhua; Mao Shun; Cui Shumao; Chen Junhong (Nanoscale Research Letters, 2011)
Abstract Carbon nanowalls (CNWs), two-dimensional "graphitic" platelets that are typically oriented vertically on a substrate, can exhibit similar properties as graphene. Growth of CNWs reported to date was exclusively carried out at a low pressure. Here, we report on the synthesis of CNWs at atmosphere pressure using "direct current plasma-enhanced chemical vapor deposition" by taking advantage of the high electric field generated in a pin-plate dc glow discharge. CNWs were grown on silicon, stainless steel, and copper substrates without deliberate introduction of catalysts. The as-grown CNW material was mainly mono- and few-layer graphene having patches of O-containing functional groups. However, Raman and X-ray photoelectron spectroscopies confirmed that most of the oxygen groups could be removed by thermal annealing. A gas-sensing device based on such CNWs was fabricated on metal electrodes through direct growth. The sensor responded to relatively low concentrations of NO2 (g) and NH3 (g), thus suggesting high-quality CNWs that are useful for room temperature gas sensors. PACS: Graphene (81.05.ue), Chemical vapor deposition (81.15.Gh), Gas sensors (07.07.Df), Atmospheric pressure (92.60.hv)